Intracardiac Sarcoma Arising From Metastasis of a Primary Phyllodes Tumor of the Breast - Donovon Allen; Kara Morton; Mustafa Ahmed; Stephen Clarkson; Silvio Litovsky; Jori May; Vanessa Eulo (Annals of Internal Medicine: Clinical Cases)
A 57-year-old woman with a malignant phyllodes tumor of the breast and recent bilateral pulmonary emboli presented with an incidental intracardiac mass on transthoracic echocardiography. Because of concern for clot burden aspiration, thrombectomy was performed. Pathology findings were consistent with spindle-cell sarcoma and histologically similar to the malignant phyllodes breast tumor. Current treatment strategies for this condition include chemotherapy and surgery. Aspiration thrombectomy typically is performed for retrieval of venous thromboemboli; however, our case suggests the procedure may be another diagnostic and therapeutic option for malignant cardiac tumors.